Gender differences in cognitive improvements after two months of atypical antipsychotic treatment in first episode schizophrenia - Li, Wanyi; Cao, Xiang; Liang, Qian; Li, Yan; Zhou, Chao; Du, Jinglun; Xie, Shiping (Frontiers in Psychiatry, 2024)
Aims This study aims to explore the gender differences in cognitive improvements after two months of atypical antipsychotic treatment in first episode schizophrenia (FES). Methods 82 patients with FES, including 50 male patients and 32 female patients, were enrolled in the present study. Positive and Negative Syndrome Scale (PANSS) and MATRICS Consensus Cognitive Battery (MCCB) were respectively conducted to evaluate the clinical symptoms and cognitive function of patients with FES at baseline and after treatment. Repeated measure ANOVA was performed to compare gender differences in cognitive domains scores between baseline and 2-month follow-up. Stepwise liner regression model was performed to explore the effect factors of cognitive improvements in patients. Results There was no significant difference in age of onset, education years, PANSS scores, duration of untreated psychosis and Olanzapine equivalent doses between male and female patients (all p > 0.05). In the comparisons of cognition function, male patients exhibited better performance in social cognition compared with female patients at baseline (t = 3.20, p < 0.05). After treatment, improvements of attention/vigilance and working memory were both found in male patients and female patients (attention/vigilance, F = 11.867, p < 0.05; working memory, F = 18.265, p < 0.05). In addition, improvement of speed of information processing was only found in female patients (F = 11.65, p < 0.01). Significant interaction between time and gender was found in speed information of processing (F = 4.140, p = 0.045). Stepwise liner regression model revealed that improvements of negative symptoms promote improvements of cognitive function in female patients (all p < 0.05). Conclusions Our findings revealed gender differences of cognitive improvements in patients with FES after 2-month treatment. It provides new evidence for gender differences in cognitive symptoms of schizophrenia, and also provides preliminary clues for further individualized cognitive intervention strategies.